Asian Development Experience Vol. 3 : Regional Co-operation in Asia - Hirono, Ryōkichi (Book collections on Project MUSE., 2003)
As ASEAN Vision 2020 proclaims, the members of ASEAN have achieved remarkable success in economic growth, stability and poverty reduction, over the past decades. There are, however, still diverse debates as to the factors which contributed to the success, with no conclusive assessment. This volume reviews the domestic reforms effectively introduced by ASEAN members after the 1997 financial crisis and what could be done to accelerate such reforms. With the entry of the 4 new members into AS ...